PLC-BASED SIMULATOR TO CONTROL THE ROAD TRAFFIC THROUGH OPERATING THE ANALOGOUS OF BRIDGE BODIES ON TWO WATER CANALS FOR THE SHIP-PATH SYSTEM - Ichsan Maulana; Arief Goeritno (Jurnal Teknologi Bahan dan Barang Teknik, 2021)
The essence of this research relates to the redesign for the acquisition of a simulator based on an embedded system in general and specifically to the utilization of a set of programmable logic controllers (PLCs). The research was chosen on the use of instrumentation systems and controlled automation mechanisms by a PLC which functioned as a simulator to operate the double bridge bodies analogy for road traffic lanes, i.e., highways on crossings with dual water canals as the ship-path system or ship crossings. Some results are (i) the operating principle of the simulator, it is observed for the sensors installed on the simulator, whether they are functioning as programmed into the PLC; (ii) when the auto mode of lifting the bridge body, both on bridge bodies #1 and #2, is longer than the process of lowering the bridge bodies, it is more emphasized on the existence of a gravitational force; and (iii) there is no significant time difference compared between the auto and manual mode selection. Concluding based on the four main research objectives and topics carried out that the stages for performing the simulator assisted by PLC and driven by GX Work of Mitsubishi can be realized according to the initials of idea and design for selecting and determining the hardware and software.